Pre-Treatment Assessments to Identify Treatment Components for an Adolescent with Subtype-3 Self-Injurious Behavior - Kyle W. Dawson; Amanda M. Morris; Tara A. Fahmie; Kortlyn Tawney; Carter Welch (Behavioral Sciences)
This case study explores the use of multiple pre-treatment assessments (functional analysis, reinforcer assessment, alternative self-restraint assessment, modified augmented competing stimulus assessment) to inform a comprehensive treatment package for an adolescent male exhibiting Subtype-3 automatically maintained self-injurious behavior (SIB). These assessments guided the development of a treatment package involving continuous access to competing stimuli and alternative self-restraint responses, differential reinforcement of alternative behaviors, and blocking hand-to-head hits across three contexts. The study also details many points of collaboration between the experimenters and the family and other specialists. Results showed decreases in SIB that were accompanied by a reduction in mechanical restraints and access to alternative activities.